Wine tourism and visitors' perception: a structural equation modeling approach - Silva, A. (Tourism Economics, 2012)
Wine tourism is emerging on an international level as a new product with significant economic potential and characteristics that may locate it in the paradigm of sustainable development. This paper analyses a specific wine tourism segment, Madeira wine tourism, in the global context of tourist consumer behaviour, through an examination of the perceptions of visitors to wineries. Specifically, the paper investigates the indirect influence of destination image construct on global tourist satisfaction, mediated by tourist wine involvement. A structural equation modelling (SEM) approach is used to develop and test conceptualized relationships between one exogenous and two endogenous constructs: tourist perceptions about the attractiveness of Madeira Island (destination image), tourist involvement in Madeira wine and global satisfaction constructs. The findings indicate that global tourist satisfaction is influenced directly by the tourists' level of wine involvement and indirectly by their image of Madeira Island. The policy implications of the results must be integrated into the international context of the wine tourism market segment in order to explore additional exchange profits from this economic activity, such as the impact of the country image and perceptions of the wine product on the promotion of wine tourism in Europe.